Oil from hake (Merluccius merluccius): Characterization, antioxidant activity, wound healing and anti-inflammatory effects. Issue 2 (May 2020) - Karoud, Wafa; Ghlissi, Zohra; Krichen, Fatma; Kallel, Rim; Bougatef, Hajer; Zarai, Zied; Boudawara, Tahia; Sahnoun, Zouheir; Sila, Assaâd; Bougatef, Ali
Abstract: The aim of this work was to evaluate some biological properties of hake head oil (HHO) as well its lipid composition. The fatty acid profiles showed a dominance of unsaturated fatty acids overtaking 55% of the total fatty acids. Omega-3 polyunsaturated fatty acid profiles exhibited a dominance of EPA (eicosapentaenoic acid) (3.96%) and DHA (docosahexaenoic acid) (25.39%). The antioxidant activity was determined through two different assays: DPPH scavenging activity and β-carotene bleaching by linoleic acid assay. Eighteen mice were excised on their back and divided into 3 groups, treated with sterile saline, commercial healing cream and HHO, respectively. The wound closure rate, the hydroxyproline contents and the histopathology evolution in skin tissue were elaborated. Also, the anti-inflammatory activity was studied by carrageenan-induced mouse paw edema. Mice were divided into 3 groups treated respectively with sterile saline, anti inflammatory drug reference and HHO. The anti-inflammatory evaluation of HHO in mice exhibited an important inhibition of carrageenan-induced hind paws edema, as confirmed by the histological analysis, the superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) level. HHO displayed a significant wound healing effect probably due to the anti-inflammatory and antioxidant activities of its EPA and DHA contents. The overall results proved that HHO might be favorable drugs who exert a great therapeutic potential wound healing and anti-inflammatory effects in animal model. Highlights: Hake Head Oil (HHO) was extracted and characterized. HHO show a dominance of Omega-3 polyunsaturated fatty. HHO exhibit a potent healing capacity on rat wounds. HHO have an interesting effect on skin tissue regeneration.